CHARACTERIZATION AND SIMILARITY ANALYSIS OF 15 TOMATO GENOTYPES IN LOWLANDS BASED ON MORPHOLOGICAL CHARACTERS - Helfi Eka Saputra; Muhammad Syukur; Syarifah Iis Aisyah (Agrotech Journal, 2017)
This study aimed to obtain information about the characteristics of 15 genotypes and to study a genetic similarity of each genotype that will be used for producing superior tomato varieties in lowlands. The research was conducted from March to August 2012 at the Experimental Field Leuwikopo Bogor Agricultural University, Darmaga Bogor. The experiment used The Randomized Complete Block Design (RCBD) using a single factor of genotype with three replications. Characterization and similarity analysis used the method of principal component analysis and cluster analysis. Based on principal component analysis and cluster analysis of tomato genotypes, it can be classified into three groups: group I (IPBT1, IPBT4, IPBT8, IPBT13, IPBT58, IPBT83 and IPBT84), Group II (IPBT3, IPBT23, IPBT30, IPBT33, IPBT34, IPBT53 and IPBT57) and group III (IPBT80). Characters with an influence on the genetic diversity of each component are the size of the cork layer between the scar stalk and the size of the center of the fruit in transverse slices. The genotypes with a high genetic similarity were IPBT1 and IPBT8, while IPBT30 with IPBT80 had a low genetic similarity